Parathyroid adenoma causing spontaneous cervical hematoma: two case reports. (December 2015) - Shinomiya, Hitomi; Otsuki, Naoki; Takahara, Shin-ichi; Yasui, Rie; Sawada, Naoki; Komatsu, Hirokazu; Fujio, Hisami; Fujiwara, Hajime; Nibu, Ken-ichi
Abstract Background Although spontaneous rupture of a cervical parathyroid adenoma with extracapsular hemorrhage is rare, it may cause cervical and mediastinal hematoma, leading to potentially fatal consequences. Case presentation The first case was a 76-year-old Asian female who presented with pharyngeal discomfort and anterior chest ecchymosis. Endoscopic investigation showed submucosal hemorrhage in the pharynx and larynx. The second case was a 62-year-old Asian male who presented with anterior chest ecchymosis and suspected of a ruptured blood vessel. Both cases were diagnosed parathyroid adenoma with extracapsular bleeding by hypercalcemia, high levels of intact parathyroid hormone and presence of a nodule behind the thyroid. Both cases were treated with excision of tumor 7 months after initial presentation. After surgery, serum calcium and parathyroid hormone levels had decreased to normal level in both cases. Conclusion Extracapsular bleeding of a parathyroid adenoma should be considered in the differential diagnosis of non-traumatic neck hematoma.